Development of a Multi-Representation Electrochemistry E-Book Utilizing 3D PageFlip Technology - Syahri, Wilda; Yusnaidar, Yusnaidar (Pendidikan Kimia FKIP Universitas Jambi, 2024)
Physical Chemistry II course in the Chemistry Education Study Program is one of the subjects with an abstract nature, such as Electrochemistry materials. The abstract nature of Electrochemistry makes it difficult for students to observe the processes occurring in Electrochemical systems directly. When explained theoretically, these concepts are often challenging for students to understand. Therefore, teaching Electrochemistry requires an e-book that incorporates chemical representations, particularly multiple representations. To address this, it is deemed necessary to develop an Electrochemistry e-book based on multiple representations using 3D PageFlip. This e-book integrates multiple representations, enabling students to independently study and comprehend Electrochemistry materials while providing flexibility and convenience. An Electrochemistry e-book with multiple representations, particularly in a computer-assisted learning format, is a viable alternative to support student learning. This study aims to develop an Electrochemistry e-book using 3D PageFlip based on multiple representations. This software allows the creation of interactive and engaging educational resources. The resulting e-book aims to enhance students' individual abilities and increase their interest and motivation, which in turn is expected to improve their academic performance and learning outcomes. Moreover, this multimedia learning tool is intended to address challenges related to students' limited comprehension during classroom learning processes, accommodate individual characteristics, and offer alternative solutions to the low self-actualization of students. Through this e-book, students can revisit and explore difficult concepts, facilitating deeper understanding. The ultimate goal of this research is to produce an Electrochemistry e-book based on multiple representations across macroscopic, microscopic, and symbolic levels using 3D PageFlip. This e-book will align with the applicable curriculum and adhere to educational principles while incorporating essential educational elements. By improving concept mastery in Electrochemistry, this resource is expected to enhance students' cognitive abilities and overall learning outcomes